Reduction of reactive power losses in radial distribution system using evolutionary programming technique / Mohamad Amirul Nizam Mohamed Thari - Mohamed Thari, Mohamad Amirul Nizam (2007)
This thesis presents the study for reduction of reactive power losses in radial distribution system using Evolutionary Programming (EP) technique. The study involves the development of Evolutionary Programming engine to be written in MATLAB taking the reactive power minimization as the objective function. This study has been realized on the 30-bus distribution system. Results obtained from the experiments indicated that the proposed technique is able to reduce reactive power losses in the system.